1999
DOI: 10.1063/1.478729
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of volume polarization in reaction field theory

Abstract: Articles you may be interested inHow to measure a complete set of polarization-dependent differential cross sections in a scattering experiment with aligned reagents?In the reaction field theory of solvation, penetration of charge density outside the cavity nominally enclosing the solute leads to a volume polarization that contributes in addition to the commonly recognized surface polarization. In principle the exact volume polarization charge density is spread everywhere outside the cavity, but its effect can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 40 publications
0
74
0
Order By: Relevance
“…͑30͒ is more convenient because the PCM linear system is a symmetric one. 32,37 Other authors 34,38 choose Eq. ͑28͒ because it naturally goes to the right limit for → ϱ, i.e.,…”
Section: B Pcm Energy Functional In Terms Of Discretized Solute-solvmentioning
confidence: 99%
“…͑30͒ is more convenient because the PCM linear system is a symmetric one. 32,37 Other authors 34,38 choose Eq. ͑28͒ because it naturally goes to the right limit for → ϱ, i.e.,…”
Section: B Pcm Energy Functional In Terms Of Discretized Solute-solvmentioning
confidence: 99%
“…The nature of the empirical parameter used 16,22,45 by several workers to improve convergence can be illustrated by considering the potential produced by a net unit charge distributed uniformly over the surface of a sphere ⌫ having radius s. The surface charge density then has a constant value of 1/4s 2 everywhere on ⌫. The electrostatic potential at an arbitrary surface point, say s q , can be easily worked out analytically to obtain 1…”
Section: Empirical Convergence Parametermentioning
confidence: 99%
“…Singular integrands associated with evaluating the electrostatic potential on the cavity surface particularly hinder convergence of recent methods such as COSMO 16 ͑conductor screening model͒, the current modification of IEF-PCM 43,44 ͑integral equation formulation of the polarized continuum model͒, and SS͑V͒PE 45,46 ͑surface and simulation of volume polarization for electrostatics͒ that reliably incorporate into the surface charge density some representation of the important influences of volume polarization effects arising from solute charge penetration outside the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies 11,12,[19][20][21] the direct volume polarization is simulated as an additional surface polarization charge distribution on the cavity surface in order to reduce the computational cost. Such an approximate method is known as the SS͑V͒PE method.…”
Section: Methodsmentioning
confidence: 99%
“…The simulation approach is known as the surface and simulated volume polarizations for electrostatics ͓SS͑V͒PE͔ method. 11 Recently reported formal analyses 11,12 of the simulation have also demonstrated that in the limit of infinite dielectric constant, the simulation of volume polarization effects is automatically included in the integral equation formulation of polarizable continuum model ͑IEFPCM͒ ͑Ref. 13͒ and the conductorlike screening model ͑COSMO͒.…”
Section: Introductionmentioning
confidence: 99%